A COMBINATION OF METHOTRIMEPRAZINE, MIDAZOLAM AND GUAIPHENESIN, WITH AND WITHOUT KETAMINE, IN AN ANESTHETIC PROCEDURE FOR HORSES - Luna, SPL; Massone, F.; Castro, G. B.; Fantoni, D. T.; Hussni, Carlos Alberto [UNESP]; Aguiar, AJA (British Veterinary Assoc, 1992)
A combination of 0.5 mg/kg of methotrimeprazine, 0.1 mg/kg of midazolam and 100 mg/kg of a 10 per cent guaiphenesin solution was investigated for the induction of recumbency in 15 horses; the addition of 1.6 mg/kg of ketamine was also evaluated in 15 horses and anaesthesia was maintained with halothane in oxygen. The horses became recumbent quickly and smoothly and they recovered quietly, with little ataxia. Tachycardia occurred after induction, but no other changes from pre-operative values were observed until halothane in oxygen had been given, when hypothermia, hypotension, bradypnoea, hyperoxaemia, respiratory acidosis and decreased respiratory minute volume developed. Horses given ketamine in addition to methotrimeprazine, midazolam and guaiphenesin were easier to intubate and recovered more quickly than horses receiving only methotrimeprazine, midazolam and guaiphenesin.